Analysis of zooarchaelogical and taphonomical variability from Maripe Cave site, Santa Cruz Province, Argentinian Patagonia - Marchionni, Laura (2012)
This paper compares two zooarchaeological sub-samples, each of which comes from different areas (North chamber and South chamber) of Maripe Cave Site (Santa Cruz, Argentina). In previous papers, each chamber was interpreted as a particular microenvironment based on their specific environmental and geoarchaeological features. In both areas hunting-gatherer society occupations were recorded since the Pleistocene-Holocene transition to late Holocene. In this paper, we investigated and discussed the different agents and processes involved in the formation of each assemblage, with the aim of assessing the taphonomic variability between the two areas and discussing their integrity. In this way we analyzed bone specimens with three-dimensional assignment of Lama guanicoe (guanaco), the most common species on the site. To this purpose, we studied the bone surfaces of specimens by means of naked eye observations and binocular magnifying to 10X, which allowed us to recognize different patterns of modification. The representation of guanaco anatomical units was also discussed at each chamber according to economic utility and BMD values. The results indicate that while there was a participation of different natural agents and processes acted differently in each sector, the main accumulator agent in both sets was the human. Differences between both chambers are observed in the representation of anatomical units, in processing marks, in the conservation of specimens, and in the number and intensity performed by each natural agents and process in each sector. Each chamber evidences different taphonomic histories; the North Chamber records greater conservation and archaeological integrity while the South Chamber shows a more complex taphonomy.